Decision-making with incomplete information : a process-based study. - Koh, Lynn Shu-Yi. (2010)
This thesis extends the phenomenon of incomplete information by introducing two distinct forms of incomplete information: Missing and hidden information. With the use of agency and attribution theory, we predict the relative effects of missing and hidden information on decisionmaking in a personnel selection context. Information criticality served as a boundary condition. The experiment was a 2*2 (type of incomplete information and criticality of information) within-subjects design with repeated measures on one factor. In addition to a quantitative measure of decision outcomes, a process-based approach - verbal protocol analysis, was adopted to explore the cognitive process of the decision-maker. We found that different types of incomplete information prompted different types of attributions, and consequently different rating outcomes. Similarly, criticality of information was found to affect the attributions and ratings made on missing and hidden information candidates.